2020
DOI: 10.32479/ijeep.10580
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Consumption and Capacity Utilization in Nigeria

Abstract: The study investigated the effects of electricity consumption on capacity utilization in Nigeria from 1981 to 2017. The study made use of annual time series data which were sourced from Central Bank of Nigeria (CBN) Statistical Bulletin (2018) and World Development Indicators (WDI). Unit root test of Augmented Dickey-fuller (ADF) and Philip Perron (PP) were used for preliminary test with Johansen co-integration test. The study employed Normalized co-integration and vector error correction mechanism in analyzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The epileptic electricity supply and its impact on manufacturing sector output in Nigeria have attracted considerable research, albeit with different conclusions. Some studies have shown that the relationship is positive and significant (Akinbola, Zekeri, & Idowu, 2017;Ekene & Mbobo, 2019;Ibrahim, Mukhtar, & Gani, 2017;Onwe & King, 2020;Ugwoke, Dike, & Elekwa, 2016) some revealed that it is positive and insignificant (Agbede & Onuoha, 2020;Chinedum & Nnadi, 2016;Kassim & Isik, 2020) and others showed that the relationship is negative (Asaleye, Lawal, Inegbedion, & Omowumi, 2021;Lawal & Owoicho, 2021). Against this backdrop, this study contributed to the existing debate by investigating the impact of electricity supply on manufacturing sector output in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The epileptic electricity supply and its impact on manufacturing sector output in Nigeria have attracted considerable research, albeit with different conclusions. Some studies have shown that the relationship is positive and significant (Akinbola, Zekeri, & Idowu, 2017;Ekene & Mbobo, 2019;Ibrahim, Mukhtar, & Gani, 2017;Onwe & King, 2020;Ugwoke, Dike, & Elekwa, 2016) some revealed that it is positive and insignificant (Agbede & Onuoha, 2020;Chinedum & Nnadi, 2016;Kassim & Isik, 2020) and others showed that the relationship is negative (Asaleye, Lawal, Inegbedion, & Omowumi, 2021;Lawal & Owoicho, 2021). Against this backdrop, this study contributed to the existing debate by investigating the impact of electricity supply on manufacturing sector output in Nigeria.…”
Section: Introductionmentioning
confidence: 99%